(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
Stand out the present research study aims at investigating the effect of applying international accounting standards in the public sector for the purpose of arriving at measurement and accounting disclosure of the employees’ benefits granting to economic units in the government sector that apply the government accounting system, and to explicate the level of benefit in improving the outputs of the accounting system and its ability to support indicators of transparency and disclosure. In view of the vast development in financial reporting, preparing reports and financial statements with a high level of transparency and disclosure as well as the importance of working individuals being one of the important and essential factors to ensure the proper functioning of work, the continuity of productivity and the efficiency of the economic unit, the government accounting system currently adopted in some public sector directorates is considered insufficient to the requirements of internationally accepted accounting standards in general The importance of the present study has emerged in finding that it is possible to apply IAS 19 employee benefits by adapting the current government accounting system in the Iraqi economic units to the requirements of the standard and getting to know the effect of the application on the information content and outputs of the government accounting system. The General Directorate of Education / Wasit has been chosen a sample for the study in question, The current study has arrived at a number of conclusions as follows: • The classification of benefits granted to employees and workers according to the government accounting system differs from the classification stated in IAS 19 Employee benefits. • The quality of financial reports and statements is an important means of disclosure and communication of financial and non-financial information. . The government accounting system does not provide adequate accounting measurement and disclosure about employee benefits. 3 In view of the findings reached at, the current study recommends the following: 1- Giving due importance to what was stated in the International Accounting Standard regarding the classification of the benefits granted and the adaptation of the government accounting system to those classifications. 2- Enhancing the awareness of management and employees in the economic unit of the importance of preparing financial reports and statements. 3- Working on adapting the government accounting system to keep pace with the requirements of international accounting standards by adding new sub-accounts to the accounting guide and creating a plan for new sub-accounts to the accounting guide and creating a plan for employee benefits.